Women's bodies, menstruation and marketing "protection:" interpreting a paradox of gendered discourses in consumer practices and advertising campaigns. Issue 6 (1st November 2016) - Malefyt, Timothy de Waal; McCabe, Maryann
ABSTRACT: This essay explores the various associations, conflicts, and resolutions that converge in consumer research to produce an advertising campaign for a feminine hygiene product. Ethnographic research identified a correspondence in beliefs and values among women who discuss menstruation as a natural process of rhythms and flow in their changing bodies. Building off the work of gender discourses in advertising, this paper claims women's "natural" discourse located in research differs from "protection" discourse in advertising, which holds a binary view of menstruation and associates menstruation socially with shame and secrecy. The research reveals that while women adopt a "natural" discourse of menstruation, discourses of "protection" still dominate marketing. Paradoxically, women incorporate both discourses in assemblages of constructing "feminine identities." This research proposes a correspondence model that regards the consumption of consumer personal-care products in terms of embodiment rather than binary categories as a way to interpret such paradoxes.